Antioxidant Activity of Selected Commercial Seaweeds - Ismail, Amin; Tan, Siew Hong (Nutrition Society of Malaysia, 2002)
This study aims to evaluate the antioxidant activity (total antioxidant and free radical scavenging activities) of seaweeds commercially available in the Malaysian supermarket. Four types of seaweeds namely Nori (Porphyra sp.), Kumbu (Laminaria sp.), Wakame (Undaria sp.) and Hijiki (Hijikia sp.) were used in the study. The extracts were prepared with water and ethanol, respectively. The β-carotene bleaching and 1,1-diphenyl-2-picrylhydrazyl (DPPH) assays were used to determine antioxidant properties of seaweeds by measuring the decrease in absorbance at 470 and 517 nm. In water extract, Kumbu showed the highest total antioxidant activity of 63% compared with other samples. Kumbu, Nori and Hijiki exhibited higher radical scavenging activity than Wakame when extracted with water. Wakame exhibited the highest antioxidant and free radical scavenging activities in ethanolic extract with 58% and EC50 = 0.42 mg/ml respectively. The results of ANOVA analysis show significant differences (p<0.05) in the means of total antioxidant and free radical scavenging activities of the seaweeds. The results showed that processed commercial seaweeds exhibited varying degrees of antioxidant properties.